2005
DOI: 10.1099/ijs.0.02465-0
|View full text |Cite
|
Sign up to set email alerts
|

Spiroplasma atrichopogonis sp. nov., from a ceratopogonid biting midge

Abstract: Spiroplasma sp. strain GNAT3597T was isolated from the biting midge genus Atrichopogon (Diptera: Ceratopogonidae). It was serologically distinct from other Spiroplasma species, groups or subgroups. Dark-field microscopy of the cells revealed the classical helical shape and subsequent transmission electron microscopy revealed cells surrounded by only a cell membrane (i.e. lacking a cell wall). Growth of strain GNAT3597T occurred in M1D medium at 30 °C. Strain GNAT3597T catabolized both glucose and arginine, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…insolitum and S . atrichopogonis , which were isolated from a fall flower and a biting midge (Diptera: Ceratopogonidae) respectively 59, 60 . Neither S .…”
Section: Resultsmentioning
confidence: 99%
“…insolitum and S . atrichopogonis , which were isolated from a fall flower and a biting midge (Diptera: Ceratopogonidae) respectively 59, 60 . Neither S .…”
Section: Resultsmentioning
confidence: 99%
“…atrichopogonis (Koerber et al. 2005), which is associated with the biting midges Atrichopogon spp. (Diptera: Ceratopogonidae), revealed that the massive gains of novel genes have occurred prior the divergence of these two Mirum clade species.…”
Section: Recent Progress In Facultative Insect Symbiontsmentioning
confidence: 99%
“…The paper in which S. leucomae was described is so inadequate that a search for the roots of its errors, omissions and misrepresentations is in order. One such root can be found in the paper describing Spiroplasma atrichopogonis (Koerber et al, 2005). In this paper, many of the difficulties outlined above also apply.…”
Section: Another Recent Paper In Spiroplasma Systematicsmentioning
confidence: 86%